Influence of volumetric oxygen transfer coefficient (kLa) on xylanases batch production by Aspergillus niger van Tieghem in stirred tank and internal-loop airlift bioreactors - Michelin, Michele (2013)
Oxygenation is an important parameter involved in the design and operation of mixing-sparging bioreactors and it can be analyzed by means of the oxygen mass transfer coefficient (kLa). In this study, batch fermentations in stirred tank bioreactor (STB) and airlift bioreactor (ALB) were operated under a range of kLa values, in attempts to optimize and compare the activities of extracellular xylanase and β-xylosidase synthesized by the fungus Aspergillus niger van Tieghem, using corncob as inducer source. The higher xylanase levels were observed on STB (9000 U l−1; kLa = 30 h−1), while the β-xylosidase production was similar in both bioreactors. However, when the enzymatic activity was compared for the same kLa value (12 h−1) in STB and ALB, the xylanase and β-xylosidase productions were higher in ALB (7000 U l−1 xylanase; 2100 U l−1 β-xylosidase) than STB (4500 U l−1 xylanase; 1800 U l−1 β-xylosidase).